Regulatory Strategies for Accelerating Civil Servant Functional Promotions in Higher Education - Endang Retno Pujirahayu; Siti Mursidah; Muhammad Azil Maskur; Ricky Dermawan Fauzi (Unnes Law Journal, 2025)
This study examines a model for accelerating promotions to functional positions following the issuance of the Minister of Administrative and Bureaucratic Reform (PAN RB) Regulation Number 1 of 2023 within the Universitas Negeri Semarang (UNNES) environment. The research employs a normative legal method by analyzing existing legal and policy documents, combined with a qualitative approach to produce descriptive findings and draw conclusions from the research questions. The study addresses two main issues: (1) the key provisions in PAN RB Regulation Number 1 of 2023 that enable accelerated promotion for functional officials (Jabatan Fungsional, JF), and (2) the strategies that JF employees can adopt to optimize promotion opportunities under this regulation. Based on analysis and implementation at UNNES, the Minister of Education, Culture, Research, and Technology Decree No. 209/P/2024 has demonstrated significant progress in streamlining the promotion process for civil servant lecturers. Procedural simplification and a stronger emphasis on objective performance evaluation have positively influenced civil-service career development, particularly for academic staff. The integration of credit-score systems and digital platforms such as SISTER enhances administrative efficiency and promotes transparency in performance assessment. Overall, this research contributes to cross-sector discussions on human resource management, especially regarding performance-based appraisal, policy transparency, technology integration, and the broader impact of regulatory reforms on employee career advancement and well-being.